Perfil antropométrico e fisiológico de atletas de futsal da categoria sub-20 e adulta - Barbieri, F. A. [UNESP]; Barbieri, R. A. [UNESP]; Queiroga, M. R.; Santana, W. C.; Kokubun, Eduardo [UNESP] (Desafio Singular, Lda, 2012)
The aim of this study was to determine the anthropometrical and physiological profile of futsal players and compare between under-20 and adults categories. Twenty four male athletes futsal participated in the study. They played in two teams of futsal-level state: a team with players under-20 (12 athletes); and another with players of the adults category (12 athletes). The participants performed a routine assessment involving anthropometric measurements (body mass, size, thickness of skin folds, perimeter body and bone diameter) and tests to estimate the aerobic and anaerobic capacity. The results did not indicate differences in relation to the anthropometrical and physiological profile between the under-20 and adults categories. We concluded that the promotion of athletes from the under-20 category for the adult's category taking into account the anthropometrical profile and aerobic and anaerobic performance indicators is recommended. However, other indicators, such as the technical, tactical and psychological aspects are important to help in understanding this promotion phase and in the training. © FTCD/FIP-MOC.
Anthropometrical and physiological profile of futsal players of the under-20 and adults categories
Keywords: Aerobic and anaerobic capacity; Assessment; Futsal; Somatotype